Learning Strategies at SD Muhammadiyah 2 Sidoarjo during the Covid-19 Pandemic - Syahfrina Rahmawati (Proceedings of The ICECRS, 2021)
This research is a qualitative research which aims to obtain an overview of the implementation of online learning at SD Muhammadiyah 2 Sidoarjo as an effort to suppress the spread of Covid-19 in the school environment. The research subjects were students of SD Muhammadiyah 2 Sidoarjo. Data were collected by direct interviews. The results showed that: (1) students have taken turns learning online at home and offline (2) online learning has flexibility in its implementation and is able to encourage the emergence of independent learning and motivation to be more active in learning; and (3) distance learning encourages the emergence of social distancing behavior and minimizes the appearance of student crowds so that it is considered to reduce the potential for the spread of Covid-19 in the school environment.